Review of materials for the fabrication of microparticles in the context of bone tissue engineering / Ahmad Fareez Mohd Rawi ... [et al.] - Mohd Rawi, Ahmad Fareez; Jaapa, Khairani Hasuna; Lim, Siew Shee; Mohamed, Nur Aliana Hidayah (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Bone tissue engineering (BTE) is a rapidly advancing field that seeks to repair or regenerate damaged or diseased bone tissue. Microparticles play an increasingly significant role in BTE by serving as drug delivery systems, cellular carriers, and scaffold components. This review aims to provide a comprehensive understanding of the variety of materials used in the fabrication of microparticles for bone tissue engineering applications. Natural polymers discussed include chitosan, collagen, gelatin, hydroxyapatite (HA), and silk fibroin, each offering unique biocompatibility and biochemical properties. Synthetic polymers such as ceramics, poly (lactic acid) (PLA), poly (lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), and polycaprolactone (PCL) offer advantages in terms of mechanical stability and controlled degradation. The review also explores composite materials that combine the strengths of natural and synthetic polymers for enhanced biocompatibility, mechanical strength, and bioactivity. The functionalization and surface modification of these microparticles to meet specific requirements in bone tissue engineering are additionally covered. The objective is to guide researchers in selecting the most appropriate materials for specific applications within the realm of bone tissue engineering, considering factors such as biocompatibility, mechanical properties, and bioactivity.